Scanning Electrochemical Microscopy of Electrically Heated Wire Substrates - Wert, Stefan; Fußstetter, Alexander; Iffelsberger, Christian; Matysik, Frank-Michael (Molecules, 2020)
We report a new configuration for enhancing the performance of scanning electrochemical microscopy (SECM) via heating of the substrate electrode. A flattened Pt microwire was employed as the substrate electrode. The substrate was heated by an alternating current (AC), resulting in an increased mass transfer between the wire surface and the bulk solution. The electrochemical response of the Pt wire during heating was investigated by means of cyclic voltammetry (CV). The open circuit potential (OCP) of the wire was recorded over time, while varied heating currents were applied to investigate the time needed for establishing steady-state conditions. Diffusion layer studies were carried out by performing probe approach curves (PACs) for various measuring modes of SECM. Finally, imaging studies of a heated substrate electrode surface, applying feedback, substrate generation/tip collection (SG/TC), and the competition mode of SECM, were performed and compared with room temperature results.
Keywords: vysoká teplota; elektrody; Microscopy, Electrochemical, Scanning; Electrodes; elektrochemie; Electrochemistry; skenovací elektrochemická mikroskopie; Hot Temperature